20=4g(g-15)

Simple and best practice solution for 20=4g(g-15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20=4g(g-15) equation:



20=4g(g-15)
We move all terms to the left:
20-(4g(g-15))=0
We calculate terms in parentheses: -(4g(g-15)), so:
4g(g-15)
We multiply parentheses
4g^2-60g
Back to the equation:
-(4g^2-60g)
We get rid of parentheses
-4g^2+60g+20=0
a = -4; b = 60; c = +20;
Δ = b2-4ac
Δ = 602-4·(-4)·20
Δ = 3920
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{3920}=\sqrt{784*5}=\sqrt{784}*\sqrt{5}=28\sqrt{5}$
$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(60)-28\sqrt{5}}{2*-4}=\frac{-60-28\sqrt{5}}{-8} $
$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(60)+28\sqrt{5}}{2*-4}=\frac{-60+28\sqrt{5}}{-8} $

See similar equations:

| 63=31-4(x-3) | | 2(p-14)=2 | | -2x+6x+26=3x-22 | | 2(p-4)=2 | | 6b^2=b^2+7-b | | 4(x-5)+4x=-24+2x | | h=16^2+48+3 | | 6(t-88)=24 | | −2+5x=4x+2 | | h+72/2=3 | | 3=j/3-5 | | 3x+6-4x=24+5x | | s+6/9=3 | | 5(g-74)=90 | | 70+35h=1 | | q+27/9=7 | | 6=z-56/7 | | 2b=5=19 | | 3=−15c+8 | | 50-2x=24 | | 9x/4=6 | | 2x+36-16=16x | | 6n+11=7+4(1+8n) | | 9t+3=6t+15 | | x(-7)=63 | | 2(1+b)=-7+5b | | 5-3x-3=25 | | 8-1.8=1.2x | | -3-7(2+4x)=95 | | 3(l+6)=39 | | (2x+3)=(4x+20) | | 2g-g+4=17 |

Equations solver categories